2017
DOI: 10.1039/c6nr08486a
|View full text |Cite
|
Sign up to set email alerts
|

Design of nanocarriers for nanoscale drug delivery to enhance cancer treatment using hybrid polymer and lipid building blocks

Abstract: Polymer-lipid hybrid nanoparticles (PLN) are an emerging nanocarrier platform made from building blocks of polymers and lipids. PLN integrate the advantages of biomimetic lipid-based nanoparticles (i.e. solid lipid nanoparticles and liposomes) and biocompatible polymeric nanoparticles. PLN are constructed from diverse polymers and lipids and their numerous combinations, which imparts PLN with great versatility for delivering drugs of various properties to their nanoscale targets. PLN can be classified into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
96
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 180 publications
0
96
0
2
Order By: Relevance
“…Various PLN formulations were prepared by sequential two‐step sonication followed by a self‐assembly process using the formulation compositions presented in Table S1 of the Supporting Information . The particle properties ( Figure a, Figure S3, Supporting Information) indicate that these PLNs are suitable for intravenous (i.v.)…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Various PLN formulations were prepared by sequential two‐step sonication followed by a self‐assembly process using the formulation compositions presented in Table S1 of the Supporting Information . The particle properties ( Figure a, Figure S3, Supporting Information) indicate that these PLNs are suitable for intravenous (i.v.)…”
Section: Resultsmentioning
confidence: 61%
“…Prior to making the PLN system, we carefully reviewed properties of unsaturated liquid lipids and identified two candidates of unsaturated fatty acids (FA), i.e., a mono‐unsaturated FA oleic acid (OA) and a poly‐unsaturated fatty acid DHA. Incorporation of low melting temperature FA (i.e., OA or DHA) into PLN could spatially create amorphous form within its solid lipid matrix, thus improving drug loading, colloidal stability and reducing initial burst drug release . Our previous study of mono‐unsaturated OA (unpublished data) showed that PLN made of binary mixtures of OA and a solid lipid improved physicochemical stability and increased encapsulation of a hydrophilic drug (i.e., doxorubicin) via ionic interactions compared to PLN composed only of solid lipids .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past several decades, nanoparticles are one of the most studied functional materials for cancer therapy with the aim to improve drug solubility, protect the drugs from premature degradation, prolong their blood circulation time, enhance the drug accumulation at the targeted site, and facilitate drug intracellular penetration, thus achieving higher efficiency and lower toxicity . Among various nanocarriers, liposomes are widely considered to be one of the most successful and most promising formulations for efficient anticancer drug delivery, due to their biocompatibility and biodegradability, simplicity in preparation, and flexibility in functionalization .…”
Section: Introductionmentioning
confidence: 99%